2015
DOI: 10.1039/c5ra15373e
|View full text |Cite
|
Sign up to set email alerts
|

A simple and reversible fluorescent probe based on NBD for rapid detection of hypochlorite and its application for bioimaging

Abstract: A simple and reversible fluorescent probe bearing 7-nitrobenz-2-oxa-1,3-diazole and a selenomorpholine fragment was designed and synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Due to the PET from Se to coumarin, CM1 showed fluorescence "OFF" in PBS buffer. In the presence of HOCl, the fluorescence of CM1 was switched "ON" within seconds, making it a good candidate for real-time By employing other fluorophores [105,123,[193][194][195][196][197][198][199][200], such as pyrene [87,88,201], phenanthroline [94,202], phenothiazine [100,[203][204][205], carbazole [93], NBD [206][207][208], MB [209], TPE [210], benzothiazole [211,212], phenanthroimidazole [96,213], and cyanine (Cy) [119,214]…”
Section: <Fig 8 Is Here>mentioning
confidence: 99%
“…Due to the PET from Se to coumarin, CM1 showed fluorescence "OFF" in PBS buffer. In the presence of HOCl, the fluorescence of CM1 was switched "ON" within seconds, making it a good candidate for real-time By employing other fluorophores [105,123,[193][194][195][196][197][198][199][200], such as pyrene [87,88,201], phenanthroline [94,202], phenothiazine [100,[203][204][205], carbazole [93], NBD [206][207][208], MB [209], TPE [210], benzothiazole [211,212], phenanthroimidazole [96,213], and cyanine (Cy) [119,214]…”
Section: <Fig 8 Is Here>mentioning
confidence: 99%
“…Zhang et al reported the Se-containing reversible HOCl probe 38 based on 7-nitrobenz-2-oxa-1,3-diazole (NBD). [50] This probe shows highly selective, sensitive (low detection limit of 3.3 nM) and rapid (within 10 s), as well as reversible recognition to hypochlorite in the presence of GSH. Se oxidation suppresses the d-PeT process from the selenide to NBD in the excited state, making the turn-on fluorescence response of probe 38 to happen.…”
Section: Eurjocmentioning
confidence: 99%
“…Zhang and co-workersd escribed the small and reversible probe based on 7-nitrobenz-2-oxa-1,3-diazole as af luorescent moiety and selenomorpholine as ar eactive site on the probe which quenches the fluorescenceb yw ay of aP ET process (Scheme 24). [54] Because of the PET effect imparted by the selenomorpholine probe is weakly fluorescent, it therefore shows a" turn-on" response after reaction with HOCl, and again a "turn-off" response with GSH. The reversible redoxc ycle of the probe was demonstrated (up to four times in repetition) under the same conditions suggesting adequate stabilityo ft he probe which could be used to detect the oxidant in question Scheme20.…”
Section: Oxidation Of Organochalogen To Their Tetravalent (E = O) Oxidesmentioning
confidence: 99%
“…Zhang and co‐workers described the small and reversible probe based on 7‐nitrobenz‐2‐oxa‐1,3‐diazole as a fluorescent moiety and selenomorpholine as a reactive site on the probe which quenches the fluorescence by way of a PET process (Scheme ) . Because of the PET effect imparted by the selenomorpholine probe is weakly fluorescent, it therefore shows a “turn‐on” response after reaction with HOCl, and again a “turn‐off” response with GSH.…”
Section: Introductionmentioning
confidence: 99%